Problem-based learning (PBL) as an effective solution to enhance understanding of physics concepts: A systematic literature review - Ayu, Hena Dian; Chusniyah, Dina Asmaul; Kurniawati, Mega Putri; Purwanti, Putri Festiana; Lukitawanti, Sartika Dewi; Putri, Amelia Nurdevianti (Journal of Environment and Sustainability Education, 2024)
Understanding physics concepts remains a focal point of education, continually researched and sought for appropriate solutions, especially in teaching strategies. The teaching strategies employed vary greatly in influencing students' understanding of concepts. The aim of this research is to identify effective solutions in enhancing students' understanding of physics concepts, based on data obtained from various relevant journals from 2010 to 2022. This study was conducted using the Systematic Literature Review (SLR) method, utilizing databases such as ERIC, Journal of Education Research, British Education Journal, and other journals indexed by SINTA to identify, review, evaluate, and interpret available research. The results indicate that an effective teaching strategy to enhance students' understanding of concepts is Problem-Based Learning (PBL).